Pengaruh Media Edukasi Cuci Tangan Terhadap Perilaku Cuci Tangan pada Anak Usia Pra Sekolah di TK ABA Gedongkiwo Yogyakarta - Lubis, Dina Putri Utami; Hanifa, Kaidahu Yanie; Priyantari, Wiwin; Istichomah, Istichomah; Handayani, Sri (HEALTHY BEHAVIOR JOURNAL, 2023)
Background: Hand washing is cleaning hands using soap and running water if hands are visibly dirty or using an alcohol-based liquid if hands are not visibly dirty. Pre-school-aged children have less awareness about hand washing behavior. Audio visual media is one of the media used to provide hand washing education. Objective: The purpose of this study is to analyze the effect of providing hand washing education using audio-visual media on hand washing behavior in pre-school children Method: The research design was a one group pretest-posttest design. The population of this study were all students at the TK ABA Gedongkiwo, Yogyakarta, 52 students in total using a total sampling technique. The independent variable was education with audio-visual media and the dependent variable was hand washing behavior. Data collection used an observation sheet according to the six steps of hand washing and four minimum hand washing time at school. Data management techniques by means of editing, coding, scoring, tabulation, data entry and data cleaning. Statistical test used the Paired Sample T-Test. Result: The results of the study from 52 respondents before being given hand washing education using audio visual media, most of the respondents behaved badly, 48 children (92.3%), after being given hand washing education using audio visual media, most of the respondents behaved well, 41 children (78.8 %). The Paired Sample T Test statistical test obtained a Sig value. (2 tailed) = 0.001 where the Sig. value (2 tailed) was less than 0.005 therefore H0 is rejected and H1 is accepted Conclusion: The conclusion is that there is an effect of providing hand washing education using audio visual media on hand washing behavior in pre-school aged children at TK ABA Gedongkiwo, Yogyakarta.